PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TPS TERHADAP HASIL BELAJAR MATEMATIKA POKOK BAHASAN TEOREMA PYTHAGORAS - Syahri, Putri (Al-Khawarizmi, 2017)
The aim of this study was to examine the influence of cooperative model type TPS toward the mathematics achievement grade 8-students of MTs Budi Agung, Medan. The true experimental design with the comparison group was used in this study. The population is grade 8-students in academic year 2013/2014 with the total of 90 students while the sample is the students of classroom VIII-1 as the experimental group and the students of classroom VIII-2 as the control group. The data were collected by using test and were analyzed by using t-test. The results showed that the average score of students’ achievements of the experimental group is 8.87 and of the control group is 7.5. It conclude that there is a significant influence of cooperative model type TPS toward the mathematics achievement of grade 8-students of MTs Budi Agung, Medan